Energy-saving hydrogen production by water splitting coupling urea decomposition and oxidation reactions. Issue 1 (6th December 2022) - Xiao, Zehao; Qian, Yinyin; Tan, Tianhui; Lu, Hongxiu; Liu, Canhui; Wang, Bowen; Zhang, Qiang; Sarwar, Muhammad Tariq; Gao, Ruijie; Tang, Aidong; Yang, Huaming
Abstract : Self-supported Ni3 S2 reconstructs into hydroxyl ligands and participates in the decomposition and oxidation of urea to ammonia and N2, achieving avoidable formation of unfavorable NiOOH and strong bond with urea derivatives to enhance self-stability. Abstract : The efficiency of hydrogen generation via alkaline water splitting is seriously restricted by the high energy barrier of anodic water oxidation with sluggish kinetics. Urea electrocatalysis holds great potential for accomplishing energy-saving hydrogen production and simultaneously relieving urea-rich sewage stress, but its real mechanism is still controversial and the lack of efficient catalysts with sustainable stability limits its further application. In this work, vertical self-supported Ni3 S2 nanosheets with boosted activity and better durability were synthesized on the nickel foam. Both experimental and theoretical results reveal a novel mechanism different from most other nickel-based catalysts that Ni3 S2 spontaneously reconstructs into surface hydroxyl ligands and directly participates in the decomposition reaction of urea to ammonia, in which hydroxyl-modified Ni sites possess strong binding ability with urea derivatives to further improve self-stability; and an oxidation reaction of urea to N2 provides electrons for maintaining ultra-low potential to avoid the formation of unfavorable NiOOH. Impressively, hydroxyl-modified Ni3 S2 requires only 1.339 V to afford 100 mA cm −2, opening up brand-new avenues for the development of urea electrocatalysis with higher nitrogen recycle efficiency and stability.